RESIDENTS’ TOURISM SUPPORT BEHAVIOUR: THE ROLE OF SUSTAINABLE TOURISM ATTITUDE - Reyhan A. Ayazlar; Gökhan Ayazlar (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2016)
Sustainability is necessary and a good alternative way to minimize tourism’s negative impacts and its long-term success. Residents have an important role for sustainable development in a touristic destination. Although there are many research to examine residents’ opinions toward tourism impacts, studies about their sustainable tourism are limited. Therefore, this study aims to measure residents’ attitude and their support to tourism. 403 data were gathered in Didim sample between March and April in 2016. Structural equation modelling was utilized for analyses. According to the results, five of seven dimensions of sustainable tourism attitude relate to residents’ support for sustainable tourism. Perceived social costs dimension is more effective on support whereas environmental sustainability has the lowest impact. Theoretical and managerial contributions are discussed.